Yield assessment of new streak-resistant topcross maize hybrids in Benin - Emeraghi Mary; Iseghohi Innocent; Idohou Jacob; Mkpuma Kenneth C.; Agbandou Pinawé C.; Afouda Leonard; Akponikpe Pierre I.; Hotegni Nicodeme V. Fassinou; Missihoun Antoine A.; Oselebe Happiness; Achigan-Dako Enoch G. (Open Agriculture)
Maize (Zea mays L.) is the foremost cereal consumed in Benin but its production is constrained by the lack of access to high-quality seeds for intensification of the crop; hence, the continued cultivation of disease-susceptible, low-yielding, and open-pollinated varieties (OPVs). The study (i) evaluated the agronomic performance and heterosis of topcross hybrids (THs) developed from a cross between new streak-resistant inbred lines and Benin-adapted OPVs, (ii) estimated the combining ability of the parental materials for grain yield (GY), and (iii) assessed the relationship between GY and other agronomic traits. Eleven OPVs were crossed to two inbred lines in a line × tester mating design to generate 22 THs. The THs were evaluated across four environments in Benin. The environment had a significant effect on GY and agronomic traits. General and specific combining ability effects were significant for GY and other traits indicating the presence of additive and non-additive gene effects. Four THs exhibited positive mid- and better-parent heterosis for GY and DMR ESR W × TZIL07A01322, which is the highest yielding TH, at 5.1 tons per hectare, had 29.1 and 13.3% yield advantages over its mid-parent and better-parent mean yields, respectively, with the potential for commercialization by indigenous seed enterprises. GY was positively associated with 100-seed weight enabling indirect selection. Four OPVs contributed favorably to observed heterosis and could serve as potential genotypes for inbred line extraction.